2017
DOI: 10.1111/gcb.13669
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of climate change on carbon storage and tree species composition in a dry deciduous forest

Abstract: Forest vegetation and soils have been suggested as potentially important sinks for carbon (C) with appropriate management and thus are implicated as effective tools in stabilizing climate even with increasing anthropogenic release of CO . Drought, however, which is often predicted to increase in models of future climate change, may limit net primary productio (NPP) of dry forest types, with unknown effects on soil C storage. We studied C dynamics of a deciduous temperate forest of Hungary that has been subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 72 publications
(73 reference statements)
2
28
1
Order By: Relevance
“…The considered environmental gradients might have been too narrow to invoke changes in tree cover or tree litter quality. Current evidence on tree species responses to global change indeed suggests that compositional changes in the tree layer are expected under more extreme climatic conditions characterized by hotter drought periods (Allen et al, ; Buras & Menzel, ; Fekete et al, ). Hence, including more southern regions of Europe could have provided more insights on this.…”
Section: Discussionmentioning
confidence: 99%
“…The considered environmental gradients might have been too narrow to invoke changes in tree cover or tree litter quality. Current evidence on tree species responses to global change indeed suggests that compositional changes in the tree layer are expected under more extreme climatic conditions characterized by hotter drought periods (Allen et al, ; Buras & Menzel, ; Fekete et al, ). Hence, including more southern regions of Europe could have provided more insights on this.…”
Section: Discussionmentioning
confidence: 99%
“…While, the quality and function, and the stability of SOC largely depend on the chemical composition and molecular structure of SOC [9]. Previous studies have shown that different revegetation types have different influences on the distribution of soil C pools [10], especially between coniferous and broadleaf forests [11][12][13]. In previous decades several studies have focused on comparing SOC at different vegetation succession stages, while there are few reports concerning the SOC chemical composition under different revegetation types.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions of the geographic, climatic, and soil conditions, and vegetation of the forest were reported in detail by Jakucs (1985Jakucs ( , 1988, Tóth et al (2013) and Fekete et al (2014). The Quercetum petraeae-cerridis community with a dominant canopy of Q. petraea and Q. cerris deciduous tree species structure is presented in the works of Mázsa et al (2005), Kotroczó et al (2007) and Fekete et al (2017); the long-term dynamics of understory shrub layer and oak seedling dynamics are described among others in works of Misik and Kárász (2010) and Misik et al (2013Misik et al ( , 2017. The plots under study were made up of evenly aged temperate, mixed species deciduous forest that was at least 110 years old and had not been harvested for more than 55 years.…”
Section: Study Sitementioning
confidence: 99%